PEDAGOGICAL PRACTICES: INTERTEXTAL DIALOGUE BETWEEN CULTURAL LANGUAGES AND THE TEACHING OF HISTORY AND AFRO-BRAZILIAN AND INDIGENOUS CULTURE - Nascimento, Sueli do [UNESP]; Roiz, Diogo da Silva (Centro Univ Nove Julho, 2021)
According to Rusen (2010), new senses can lead to new representations in the historical context of past experience, which requires new techniques. This qualitative research was carried out in the city of Aracatuba, SP, Brazil, with 49 university students from technology courses. The choice of the field of research and research population were made in connection with the subject Afro-Brazilian and Indigenous History and Culture, introduced by laws 10.639/03 and 11.645/08. The instrument applied by the teacher is based on the argumentative perspective of action research, involving researcher-teacher and academic-participants. Two argumentative questions were proposed to the students: - How do you see the participation of indigenous / black people in the history of Brazil? - What is the meaning of the words Indian / Negro in the history of Brazil? We analyzed, from the perspective of the narrative competence of historical consciousness, the Freirean naive transitive consciousness and the previous Rusenian consciousness, the possible alterations based on historical knowledge, which are intermediated by culture languages (literary books, music, films and Brazilian documentaries) from the 18th to the 21st century. The results show that the students complied with the proposals, stressing the continuity of this process in this and other higher education institutions.
Keywords: historical consciousness; afro-brazilian and indigenous history and culture; reflective education